In Vivo Antihypercholesterolemic Effects of Caricapubescens Seeds Hypercholesterolemic-induced Rats - Luhurningtyas, Fania Putri; Aprilliana, Melati; Alifa, Gea Ros (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2019)
Background: Carica is a typical plant originating from the Dieng Plateau. Carica processed products leave waste in the form of Carica seeds which have not been utilized. Based on the previous study, Carica seeds contain tannin, flavonoids, and alkaloids, so in this study, Carica seeds extract was used in the antihyperlipidemic study. Objective: To analyze the reduction of total cholesterol and secondary metabolites in the ethanol extract of Carica seeds using thin-layer chromatography.Method:Extraction was carried out by the maceration method using 96% ethanol. Antihypercholesterolemic study used 6 groups of rats Wistar strains consisting of normal group, positive control, negative control, treatment 1 (200 mg / KgBB), treatment 2 (400 mg / KgBB), treatment 3 (600 mg / KgBB). Total cholesterol level tests were carried out by using a biosystem with diasysic reagents. Statistical tests were carried out with one way ANOVA followed by LSD post hoc tests.Result: Carica seed extract has flavonoids and alkaloids. The percentage decrease in cholesterol levels in treatments 1, 2 and 3 was 15% ± 11,619, 24% ± 8,813 and 21% ± 19,471 with a significance value in the one way ANOVA test was 0,000. Conclusion: The dosage variations of Carica seed extract Affects comparable to simvastatin in reducing total cholesterol levels.